A Pedagogical Model of Rehabilitation of Maladjusted Adolescents. Salesian Experi-ences in the Context of Their Work in Italy - Bogdan Stańkowski (The Francis de Sales Scientific Society (TNFS.PL), 2022)
In this article entitled: A Pedagogical model of rehabilitation of maladjusted adolescents. Salesian experiences in the context of their work in Italy, the author raises the issue of prevention with reference to the Salesian system of education. Drawing on available literature, the author is trying to present a model of rehabilitation pedagogy adopted by the Salesians in Italy. This issue becomes a crucial problem in the article which is written in a descriptive and analytical way. The first part of the study discusses a new concept of Salesian prevention developed in the course of work with the socially maladjusted youth. In the second part, the author attempts to outline the above mentioned model of pedagogical rehabilitation which appears in the work experience of the Salesians in Italy.